Uji Mutu Fisik Tablet Ekstrak Daun Jambu Monyet (Anacardium occidentale L.) dengan Bahan Pengikat PVP (Polivinilpirolidon) secara Granulasi Basah - Dyah Susilowati; Yogi Adi Christanto (Jurnal Farmasi Indonesia, 2010)
Leaves of Anacardium occidentale L. as a diabetes mellitus drug will be made tablets. test the physical quality of tablets of Anacardium occidentale L leaves extract made by wet granulation with a binder PVP (polyvinylpyrrolidone). The extract of leaves of Anacardium occidentale L was obtained by maceration. The leaves of Anacardium occidentale L extract tablets were produced by wet granulation method. The granules are then tested for physical properties include flow time, angle of repose, drying shrinkage and moisture content. Tablets are tested for physical properties including hardness test, friability test, weight uniformity test and disintegration time. The results of this study are based on existing literature and statistical analysis to test the physical quality of the tablet. The granules obtained had a drying shrinkage of 1,16%, flow time of 5,81 seconds, and angle of repose of 24,11 0. The results of this study is the average uniformity of tablet weight is 0.642 grams. The average tablet hardness was 7.61 kg. The average number of fragility tablet is 0.13%. Average duration of crushed tablets is 5 minutes 22 seconds.